Działalność aficionados jako przykład budowania relacji społecznych wokół tradycji tauromachicznych - Ziółkowska-Kuflińska, Magdalena (Człowiek i Społeczeństwo, 2012)
Tradition in modern societies is subject to changes and modifications. Picture of this situation is, in my present condition corrida de toros in Spain. For some, it is a spectacular fight of man and bull, wiping about art or even which is an art in itself, for others it is a barbaric act of killing a bull in front of the audience. The audience of this tradition is quite specific and defined them as aficionados– enthusiasts. True enthusiasts are able to catch the slightest bullfight tradition malpractice and do not hesitate to take immediate action. The ongoing around the corrida de toros discussion in the minds of aficionados makes it the right to practice the age-old tradition is threatened. Therefore, in the last decade, are born many associations of aficionados. Of all the countless organizations aficionados (as well as a foundation), you can even replace UFTAE – Unión de Federaciónes Taurinas de Aficionados de España, Asociación Taurina Parlamentaria (ATP), association of readers “Aplausos” or Asociación de Profesionales y Aficionados Taurinos de Utrera.